If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(-1) = 0 Reorder the terms for easier multiplication: -1x = 0 Solving -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = 0 Simplifying x = 0
| 2(x-6)=24-6(x+2) | | -24=-v/4 | | 4(7s+3)-3(6s+4)= | | 3x+4(5x-6)=(38) | | x^2-4y^2+2x+8y-31=0 | | c/12=15 | | (-2x+10)+(-8x-1)=10x+-9 | | w/5=-30 | | 10x-10=55 | | 3x^2-30=-9x | | 8n+3n= | | 1/4y=20 | | -(6x-1)+6x=11 | | x=140+1.3y | | 56=5u-14 | | 3x-4y=420 | | 141.5512=2*3.14*r*7.5+2*3.14*r^2 | | 35=-2x-15-3x | | 15x-20000=24000 | | -10x(x-5)=-8(x+9) | | 2=-9+w | | 13+(5a+3)= | | 2(9-1)-5a=7 | | 3x-4x=420 | | 45x^2+94x+48=0 | | ax-w=3forw | | 7x=9(2+x) | | 1x+500=1200 | | 7x+150=15x | | 34=2v+10 | | 48-3n^2=0 | | .9*.3= |